Literasi Digital Sebagai Instrumen Mewujudkan Good Governance di Sulawesi Utara - Al Putri Abral; Susvia Delta Kusdiane; Cloudya Cartika Wowor (HK Publishing, 2026)
Abstract The rapid development of technology today is crucial for the bureaucracy to improve public services. However, enhancing technological infrastructure alone is not sufficient; it must be accompanied by the development of human resources to increase the capacity of bureaucratic actors. The qualitative research uses a literature review method and analyses how digital literacy, which consists of four pillars, can serve as an instrument to achieve good governance in North Sulawesi. The results show that digital literacy can support the implementation of effectiveness, efficiency, and responsiveness; digital culture can foster participation, consensus, and equality; digital ethics can promote transparency and accountability; and digital safety can realize the rule of law to protect citizens' personal data. This study concludes that it is necessary to improve digital literacy among human resources, not just focus on developing advanced technology. Keywords: Digital Literacy, Good Governance, Bureaucracy